Heat and Mass Transfer Over an Unsteady Stretching Permeable Surface with Non-Uniform Heat Source/Sink and Thermal Radiation - Aurangzaib, M.; Murshid, S. M.; Urooj, S. A. (The Nucleus, 2014)
In this study an analysis has been done to investigate the combined effects of heat and mass transfer over an unsteady stretching permeable surface with non-uniform source/sink and thermal radiation. The transformed nonlinear boundary layer equations are solved numerically by applying Keller-box method. The numerical results are compared and found to be in good agreement with previously published results under special cases. Finally, the influence of various embedded flow parameters on local skin friction, local Nusselt number and local Sherwood number have been analyzed through graphs carefully.